Harmonisasi dalam Proses Pembentukan Peraturan Daerah di Indonesia - Felani Ahmad Cerdas; Ali Abdurahman; Indra Perwira (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2022)
The regional authority to regulate their household affairs through Regional Regulations (Perda) raises its own problems when it is associated with harmonization of the higher laws and regulations that are parallel and often even contradict the laws. This is often an obstacle in national development within the framework of the unitary state, the weak supervision of the central government in the process of forming a regional regulation is an indicator of overlap between regional and central regulations. Factors causing legal disharmony in the formation of regional regulations can derive from internal and external institutions forming regional regulations, as the countermeasures can be carried out internally and externally. These countermeasures are the responsibility of all levels of state government, both by the provincial central government, so that the purpose of establishing good and correct regional regulations in accordance with laws and regulations and the needs of local communities can be implemented.